PENERAPAN METODE PENEMUAN TERBIMBING DENGAN MODEL PEMBELAJARAN KONSTRUKTIVISME DALAM PEMBELAJARAN MATEMATIKA MATERI BILANGAN BULAT DI KELAS VII SMP NEGERI 3 TONDANO - Bataria, Evelin Rina; Salajang, Santje M; Tumalun, Nicky K (SOSCIED, 2025)
This study aimed to determine the differences in student learning outcomes between the application of the Guided Discovery Method with the Constructivism Learning Model and Conventional Learning in improving students' understanding of integers in Class VII at SMP Negeri 3 Tondano. This research was a quasi-experimental study with a two-group pretest-posttest design. The population of this study was seventh-grade students, and the samples in this study were VII A as the experimental class, consisting of 25 students, and VII B as the control class, consisting of 22 students, at SMP Negeri 3 Tondano in the 2024/2025 academic year. The research results revealed that there was a significant difference in the average learning outcomes of students taught using the Guided Discovery Method with the Constructivism Learning Model compared to students taught using Conventional Methods. Based on the above results, it is concluded that the application of the Guided Discovery Method with the Constructivism Learning Model can improve students' understanding of integers in Class VII at SMP Negeri 3 Tondano. Thus, the Guided Discovery Method with the Constructivism Learning Model was proven effective in improving students' learning outcomes.